2021
DOI: 10.1093/humrep/deab225
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nitric oxide content mediated by asymmetrical dimethylarginine and proteinl-arginine methyltransferase 3 in macrophages induces trophoblast apoptosis: a potential cause of recurrent miscarriage

Abstract: STUDY QUESTION Is the protein L-arginine methyltransferase 3 (PRMT3)/asymmetrical dimethylarginine (ADMA)/nitric oxide (NO) pathway involved in the development of recurrent miscarriage (RM), and what is the potential mechanism? SUMMARY ANSWER Elevated levels of PRMT3 and ADMA inhibit NO formation in the decidua, thereby impairing the functions of trophoblast cells at the maternal–foetal interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
1
13
2
Order By: Relevance
“…Recently, some studies have reported increased expression of PRMT1 and PRMT3, two type I enzymes, in the endometrium of LPS-induced endometritis rats and the decidua of recurrent miscarriage patients, respectively [ 20 , 30 ]. By screening the expression levels of various PRMT mRNAs from several published gene expression profiles of endometriosis (GSE23339, GSE5108 and GSE7305), we observed that PRMT5 , a major type II enzyme, was decreased in the ectopic endometrium of endometriosis patients compared to the eutopic endometrium of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies have reported increased expression of PRMT1 and PRMT3, two type I enzymes, in the endometrium of LPS-induced endometritis rats and the decidua of recurrent miscarriage patients, respectively [ 20 , 30 ]. By screening the expression levels of various PRMT mRNAs from several published gene expression profiles of endometriosis (GSE23339, GSE5108 and GSE7305), we observed that PRMT5 , a major type II enzyme, was decreased in the ectopic endometrium of endometriosis patients compared to the eutopic endometrium of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on catalytic activity, PRMTs can be classified as a type I enzyme that catalyzes aDMA (PRMT1, PRMT2, PRMT3, PRMT4, PRMT6 and PRMT8) or a type II enzyme that generates sDMA (PRMT5, PRMT7 and PRMT9) [ 19 ]. A recent study found that aDMA content and PRMT3 expression were increased in the decidua of recurrent miscarriage patients, primarily in macrophages but not in natural killer cells or stromal cells of the decidua [ 20 ]. However, the localization and function of PRMT5, the main type II PRMT, is not clear in the endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have reported increased expression of PRMT1 and PRMT3, two type I enzymes, in the endometrium of LPS-induced endometritis rats and the decidua of recurrent miscarriage patients, respectively 20,32 . By screening the expression levels of various PRMT mRNAs from several published gene expression pro les of endometriosis (GSE23339, GSE5108 and GSE7305), we observed that PRMT5, a major type II enzyme, was sed in the ectopic endometrium of endometriosis patients compared to the eutopic endometrium of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on catalytic activity, PRMTs can be classi ed as a type I enzyme that catalyzes aDMA (PRMT1, PRMT2, PRMT3, PRMT4, PRMT6 and PRMT8) or a type II enzyme that generates sDMA (PRMT5, PRMT7 and PRMT9) 19 . A recent study found that aDMA content and PRMT3 expression were increased in the decidua of recurrent miscarriage patients, primarily in macrophages but not in natural killer cells or stromal cells of the decidua 20 . However, the localization and function of PRMT5, the main type II PRMT, is not clear in the endometrium.…”
Section: Introductionmentioning
confidence: 96%
“…Only a small proportion of ADMA is normally released into the circulation and excreted in urine. Interestingly, ADMA inhibits NOS activity, preventing nitric oxide production in macrophages in many animal models of disease [23][24][25]. However, unknown is whether inhibition of NOS by ADMA encourages the production of M2 macrophages.…”
mentioning
confidence: 99%